Assessing the predictive validity of a risk assessment instrument for repeat victimization in the Netherlands using prior police contacts - Raaijmakers, Niels (European journal of criminology, 2023)
The current study examined to what extent a valid instrument that predicts repeat victimization can be based on a victim's prior police contacts. Police records between 2010 and 2017 were retrieved for a sample of 68,229 victims. The data was split into a training set (n?=?34,224) and a test set (n?=?34,005). Using logistic regression analyses in the training set, three models were developed linking prior police contacts to repeat victimization. The predictive validity was assessed in the test set. Results indicated that (a) prior police contacts as victims, suspects and witnesses were associated with an elevated risk of repeat victimization and (b) the model correctly classified a majority of both repeat victims and non-repeat victims across various cut-off points. Findings demonstrated moderate to acceptable predictive validity, thereby suggesting that there is considerable room for improvement.